PERAN KOMISI PEMILIHAN UMUM (KPU) DALAM LITERASI POLITIK PEMILIH PEMULA PADA PEMILU PRESIDEN TAHUN 2019 DI KOTA BEKASI - Zakiah Alamanda Leandry (2022)
This study aims to discuss the role of the Bekasi City Election Commission in the political literacy of novice voters in the 2019 Presidential Election. The method used is descriptive qualitative using primary data sources and secondary data. The results of this study indicate that the Bekasi City KPU has carried out its role quite well, this can be seen from all the efforts of the Bekasi City KPU in providing socialization programs that are by the established regulations, namely Law Number 7 of 2017 and PKPU Number 10 of 2018. A series of socialization programs in the form of political education provided by the Bekasi City Election Commission contains materials that discuss political education from a procedural and substantial point of view. For example, providing an understanding of voting procedures and the voting process, as well as making people aware, especially novice voters, to use their voting rights by understanding that one vote is very important for the fate of the nation in the next five years. The author also sees that the level of political literacy of beginner voters in the 2019 presidential election in the city of Bekasi is quite good, not only seen from the presence at polling stations but also in their awareness, understanding, and skills to participate in the 2019 presidential election. The level of political literacy affects the rate of political participation. in the 2019 presidential election in the city of Bekasi increased.